Changes in blood parameters of endurance horses in 30-km training. - Lau, Su Mei; Fateh Mohamed, Bashir Ahmad; Mohd Adzahan, Noraniza; Abdullah, Rasedee (2010)
Eight endurance horses registered for competition in different categories of Sultan Cup Endurance Ride, in November 2009 were selected for an evaluation of the soundness of the horses and an examination of the changes of blood parameters in training prior to the competition. Three blood samples were taken from each horse: pre-ride, immediate post ride and 24 hours post-ride. All horses were trained at 30 km and departed at the same time and tested on the same track. Blood samples were evaluated for both haematology and biochemistry components: red blood cell (RBC), packed cell volume (PCV), white blood cell (WBC), segmented neutrophil, lymphocyte counts, electrolytes concentration, total protein (TP), aspartate aminotransferase (AST), creatine kinase (CK) and lactate. One horse was diagnosed with exertional rhabdomyolysis post-training and was removed from statistical analysis. In this study, the significant changes in most blood parameters indicated that the 30-km endurance training induced some physiological responses in horses with minimal stress and loss of water and electrolytes as reflected in the changes of blood parameters. Although elevation in serum muscle enzymes and lactate was significant, it was believed to be a normal physiological response of horses towards training without noticeable muscle injuries and/or metabolic acidosis.